Familiy and extreme poverty - Rozas, Germán (Revista de Psicología, 1999)
A highly complex subject is to surpass poverty; However, there exists a segment that it is specially tough: Extreme Poverty. This is an obstinate social political area with an accent in the economic aspect. Following this arise otjer dimensions are to be considered, among them, the family, which is fundamental and, particulary, the psychosocial variables of the family. This gives ground to the hypothesis that apects derive fromtime which conform the mother of the foundation of the Chilean poor family. This mold unfolds today a confrontation between past and modern times. This dynamic contradiction deepen.s the situation inciting a type of family associated to extreme poverty.